2005
DOI: 10.1128/jvi.79.11.6703-6713.2005
|View full text |Cite
|
Sign up to set email alerts
|

Interaction with CD4 and Antibodies to CD4-Induced Epitopes of the Envelope gp120 from a Microglial Cell-Adapted Human Immunodeficiency Virus Type 1 Isolate

Abstract: We previously showed that the envelope glycoprotein from an in vitro microglia-adapted human immunodeficiency virus type 1 isolate (HIV-1 ) is able to use lower levels of CD4 for infection and demonstrates greater exposure of the CD4-induced epitope recognized by the 17b monoclonal antibody than the envelope of its parental, peripheral isolate (HIV-1 Bori ). We investigated whether these phenotypic changes were related to a different interaction of their soluble monomeric gp120 proteins with CD4 or 17b. Equil… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
10
0

Year Published

2006
2006
2019
2019

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 17 publications
(12 citation statements)
references
References 90 publications
2
10
0
Order By: Relevance
“…BIACORE analysis showed that Envs with N283 compared with T283 have an increased affinity for CD4 due to a decreased dissociation rate from CD4. A similar mechanism was demonstrated for BORI15, a primary blood isolate adapted to replicate efficiently in microglia that has reduced dependence on CD4 (40). These findings suggest that N283 enhances HIV infection of macrophages and microglia by increasing the capacity of Envs to use the low CD4 levels expressed on these cells for fusion and entry and support a model in which HIV can acquire enhanced neurotropism by lowering the threshold levels of CD4͞CCR5 required for infection.…”
Section: Discussionsupporting
confidence: 67%
“…BIACORE analysis showed that Envs with N283 compared with T283 have an increased affinity for CD4 due to a decreased dissociation rate from CD4. A similar mechanism was demonstrated for BORI15, a primary blood isolate adapted to replicate efficiently in microglia that has reduced dependence on CD4 (40). These findings suggest that N283 enhances HIV infection of macrophages and microglia by increasing the capacity of Envs to use the low CD4 levels expressed on these cells for fusion and entry and support a model in which HIV can acquire enhanced neurotropism by lowering the threshold levels of CD4͞CCR5 required for infection.…”
Section: Discussionsupporting
confidence: 67%
“…However, these adapted Envs share several common properties, such as enhanced coreceptor interactions, increased exposure of the coreceptor binding site, increased neutralization sensitivity, and enhanced fusogenicity. These properties are also shared with BORI-15, a blood-derived virus adapted for replication in microglia [82,84], and UK1-br, a primary, neurovirulent, brain-derived isolate from a patient with HIVE and HAD [56]. Several neurotropic strains of HIV share these characteristics [83,107,150].…”
Section: Reduced Ccr5/cd4 Dependence Of Neuro-tropic Hiv and Role In mentioning
confidence: 86%
“…These syncytia resemble the multinucleated giant cells in brain that are frequently associated with HIVE and HAD. Determinants of reduced CD4 dependence in the BORI-15 Env were mapped primarily to the V1V2 variable loop regions of gp120 [129], and a recent study demonstrated that the gp120 of BORI-15 has an increased affinity for CD4 [84]. Other studies of HIV or SIV Envs also mapped determinants of reduced CD4 dependence or CD4 independence to the V1V2 regions [20,70,115,116,155].…”
Section: Reduced Ccr5/cd4 Dependence Of Neuro-tropic Hiv and Role In mentioning
confidence: 96%
See 1 more Smart Citation
“…2A) and the biochemical data indicating that the monomeric forms of the gp120s from both of these strains bound and were affected by HNG-105 (Table 1). The major differences between these isolates (23,24,32), coupled with the localization of the potential binding site for HNG-105 (4; Gopi et al, unpublished), suggest that one mechanism by which an isolate can be resistant to HNG-105 may be conformational masking of the binding site in the context of the viral spike (17,18). This concept of differential access to the HNG-105 binding site, which is thought to reside within the gp120 inner domain, is currently under investigation in our laboratory.…”
mentioning
confidence: 99%